2016
DOI: 10.1159/000444364
|View full text |Cite
|
Sign up to set email alerts
|

IgE Reactivity of Recombinant Pac c 3 from the Asian Needle Ant <b><i>(Pachycondyla chinensis)</i></b>

Abstract: Background: Stings from the Asian needle ant are an important cause of anaphylaxis in East Asia. A 23-kDa protein homologous to antigen 5 is the major allergen produced by these ants. In this study, we aimed to produce a recombinant antigen 5 allergen, Pac c 3. Methods: Recombinant Pac c 3 allergen from the Asian needle ant was expressed in Pichia pastoris and purified by ammonium sulfate precipitation and Ni affinity chromatography. IgE reactivity was demonstrated by ELISA and immunoblotting. Results: The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Jeong et al recently recombinantly expressed Pac c 3 from needle ants and showed its cross-binding with Ves v 5 by ImmunoCAP 263. …”
mentioning
confidence: 99%
“…Jeong et al recently recombinantly expressed Pac c 3 from needle ants and showed its cross-binding with Ves v 5 by ImmunoCAP 263. …”
mentioning
confidence: 99%
“…Neste sentido, cabe salientar que a reação de anticorpos bovinos específicos evidenciou uma maior reatividade à rBm86-CG obtida com sulfato de amônio em comparação a acetona e metanol. Além disso, a precipitação por sulfato de amônio permite que a amostra seja concentrada e submetida à purificação por cromatografia sem prejuízos a sua imunogenicidade (JEONG et al, 2016;KWON, 2012;LI et al, 2015;MA, 2013).…”
Section: Resultados E Discussão Precipitaçãounclassified
“…Na-ASP-2, a candidate hookworm vaccine, belongs to this family and its administration was associated with generalized urticarial reactions in several volunteers [26]. Cross-reactivity has been reported between Ag5/CAP family members with moderate sequence conservation; this is the case of Pac c 3, a Chinese ant allergen, and Ves v 5, a relevant wasp allergen, which share 50% sequence identity [27]. It is worth mentioning that a lack of cross-reactivity has also been reported for Sol i 3 and Ves v 5, which share 44% sequence identity, but with limited conservation of surface chemical properties and topology [28].…”
Section: Discussionmentioning
confidence: 99%
“…For most Ag-5 related members, production in eukaryotic hosts has been preferred due to their high content of disulfide bridges [27, 28]. It is possible that sensitization rates are underestimated; however, since PU is considered a cellular mediated disease, it is expected that the repertoire of linear T-cell epitopes of this recombinant product is completely representative of the natural molecule.…”
Section: Discussionmentioning
confidence: 99%